The labour share, government expenditure and income inequality of post-soviet countries - Bruno S. Sergi; Svetlana P. Balashova; Svetlana Ratner (Economies, 2023)
This study analyses the influence of economic growth on inequality, concentrating on the role of governments as mediators. The period studied is from 2000 to 2020, encompassing 11 post Soviet countries. The primary estimation method used is the two-stage least squares for panel data. Despite the differences in the economic and political systems at the current development stage, the post-Soviet countries share a common pattern in terms of the relationship between economic growth, the labour income share and the level of inequality, which we first show in this article. Government expenditure has the potential to reduce inequality. However, its effectiveness depends largely on government efficiency and the development of democratic institutions. Despite the increase in government spending on education, more is needed to reduce income inequality. Increased economic performance, productivity, and high-quality state institutions are necessary for this change.
Keywords: 330; labour share; income inequality; post-Soviet countries; government expenditures; incomedistribution; TSLS